Field and laboratory observations of down-slope bentonite migration in exposed composite liners. Issue 5 (October 2016) - Rowe, R. Kerry; Brachman, Richard W.I.; Take, W. Andy; Rentz, Amy; Ashe, Lauren E.
Abstract: GCL manufacturers recommend that composite liners (i.e., a geomembrane (GMB) over geosynthetic clay liner (GCL)) be covered in a timely fashion. This paper highlights the importance of following this recommendation by reporting on significant down-slope bentonite migration first noted at the Queen's University Environmental Liner Test Site (QUELTS) constructed in 2006 (QUELTS I). The down-slope erosion is attributed to thermal cycles that caused evaporation of moisture from the GCL on sunny days (when the black geomembrane heated to 60–70 °C) followed by condensation of moisture on the underside of the geomembrane at night when the geomembrane cooled. The condensed moisture would drip onto the GCL and run down-the slope. Repetition of this process over an extended period of time caused the erosion of bentonite at some locations in all four GCLs examined in the 3.7 years the liner was exposed before the full inspection of the GCL which detected the mechanism. A series of laboratory experiments confirmed that dripping of evaporative water could cause down-slope erosion in relatively few cycles. These tests also identified several GCL products with a high resistance to down-slope erosion prompting the desire to construct a second field study to examine the issue. Thus, in 2012, the liner system was removed and QUELTS II was constructed with a new series of 7 composite liners. This paper highlights the key findings from these studies with particular emphasis on issues of importance to designers, regulators and installers.